The Development of Substitute Object Pretense: The Differential Importance of Form and Function. Issue 2 (14th March 2016) - Hopkins, Emily J.; Smith, Eric D.; Weisberg, Deena Skolnick; Lillard, Angeline S.
Abstract : Substitute object pretense is one of the earliest-developing forms of pretense, and yet it changes considerably across the preschool years. By 3.5 years of age, children can pretend with substitutes that are highly dissimilar from their intended referents (Elder & Pederson, 1978), but even older children have difficulty understanding such pretense in others (Bigham & Bourchier-Sutton, 2007). The present studies had 3 aims: 1) to examine the relative influence of the form and function of substitute objects; 2) to replicate the age gap between pretense production and comprehension using a tightly controlled procedure; and 3) to investigate whether preschoolers' comprehension of substitute object pretense is predicted by a) theory of mind (ToM), because it involves reading pretender intent, and (b) executive function (EF), because it involves inhibiting the substitute object's identity. In Study 1, 3- to 5-year-old children performed at ceiling on a test of substitute object pretense production, whereas pretense comprehension improved considerably across this age range. Study 2 provided evidence that the function of a substitute object is more influential than its form in determining whether a child can comprehend pretense actions with the object. The results of Study 2 also provided support for the role of ToM in comprehending another's pretense. Finally, Study 3 replicated the results regarding form, function, and ToM in a sample drawn from a different community. The effects of EF on pretense comprehension were inconsistent across conditions and studies, suggesting that EF may not play a major role in the comprehension of pretense with substitute objects.